DNA methylation of the oxytocin receptor interacts with age to impact neural response to social stimuli - Puglia, Meghan H.; Lynch, Morgan E.; Nance, Madelyn G.; Connelly, Jessica J.; Morris, James P. (Frontiers in Aging Neuroscience, 2023)
Introduction Social isolation is one of the strongest predictors of increased risk of mortality in older adulthood. The ability to form and maintain the social relationships that mitigate this risk is partially regulated by the oxytocinergic system and one’s ability to attend to and process social information. We have previously shown that an epigenetic change to the DNA of the oxytocin receptor gene (OXTR methylation) affects the salience of social information in young adults. Little is known about how the oxytocinergic system ages and what effect this aging system has on social cognitive abilities throughout the lifespan. Methods Here we explored age-related differences in the association between neural response during selective social attention and OXTR DNA methylation in young (age 18–31) and older (age 58-81) adults. Participants underwent fMRI during a selective social attention task and provided a DNA sample for the assessment of OXTR methylation. Results and Discussion We found that older adults activated diffuse areas of visual cortex and dorsolateral prefrontal cortex during selective social attention, consistent with the dedifferentiation and compensatory neural activation commonly reported in aging. We found a significant age-by-OXTR methylation interaction on neural response when attending to social stimuli in a complex display; young adults displayed a positive association between OXTR methylation and neural activation, replicating our prior finding that young adults with presumed diminished endogenous access to oxytocin recruit regions of the attentional cortex to a greater extent. This association did not hold for older adults. Instead, perceived social support interacted with OXTR methylation to influence neural response during selective social attention. These data suggest that environmental factors like social support moderate biological processes in aging and highlight the importance of a lifespan perspective for understanding associations between individual differences in the oxytocinergic system, neural function, and social behavior.